PENGETAHUAN, SIKAP DAN KEPEDULIAN MAHASISWA PASCASARJANA ILMU LINGKUNGAN TERHADAP LINGKUNGAN HIDUP KOTA JAKARTA - Veronica Kumurur (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2013)
Environmental issues is a very complex problem that must be overcome, one of them is, water pollution, air, social conflict, and many other things that happened in Jakarta, it takes a conscious effort from the community, and students who cared to be able to help solve the problem. This study aims to: (i) to determine the extent to which knowledge, attitudes and environmental science student concern for the environment in Jakarta; (ii) to test / analyze whether there is a relationship between gender, age of the knowledge, attitudes and awareness of environmental science students environment in Jakarta. From the research results obtained that knowledge, attitudes and environmental science student concern for the environment in Jakarta, as follows: (i) the majority of respondents or 50% -58% of respondents have a good score on knowledge about the environment; (ii) there 53% -65% of the respondents realized that his wrong in maintaining environmental quality in Jakarta; (iii) environmental awareness is still low, is evident from respondents' answers caring instruments, where the answer is rarely involved (JT) is the best answer a lot of responsibility (40% -53%). From the results of testing the relationship between the variables gender, age environmental science graduate students with the knowledge, attitude and concern for the environment in Jakarta obtained the conclusion that: (i) sex was not associated with attitudes, sex-related knowledge about the environment and gender not associated with concern for environmental quality in Jakarta; (ii) age has nothing to do with student attitudes toward environmental science, age was not associated with knowledge about environmental quality in Jakarta, but age-related concerns environmental science graduate students; (iii) knowledge related to environmental science student attitudes, knowledge is also associated with concern for environmental quality in Jakarta; (iv) the attitude is not related to concern for environmental quality in Jakarta